Motivasi melakukan fraud dan faktor-faktor yang mempengaruhinya - Prapti Antarwiyati; Raras Ega Purnomo (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2017)
This research aims to analyze the factors that motivate a person to perform fraud. These factors include, organizational justice, internal control, compliance compensation, and information asymmetry. The research data obtained from the results of questionnaires collection of 52 respondents who are employees of Bank Perkreditan Rakyat Bank Bantul, Yogyakarta Special Region. Hypothesis testing in this research using multipleregression model with SPSS software. The results of this research indicate that organizational justice and internal control significantly negatively affect the motivation to perform fraud. Compliance suitability does not affect the motivation to perform fraud. Information asymmetry has a significant positive effect on the motivation to perform fraud. Company leaders or equals are expected to continue to maintain and maintain justice organization that has been formed in the company. The company is also expected to always enforce an effective internal control system and continue to evaluate the internal control system that has been operating in the company. In addition, the provision of information should be balanced in accordance with the needs so that no use of excessive information that can motivate someone to commit fraud.